Systems Engineering Agile Design Methodologies - Crowder, James A.; Friess, Shelli; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book examines the paradigm of the engineering design process. The authors discuss agile systems and engineering design. The book captures the entire design process (functionbases), context, and requirements to affect real reuse. It provides a methodology for an engineering design process foundation for modern and future systems design. This book captures design patterns with context for actual Systems Engineering Design Reuse and contains a new paradigm in Design Knowledge Management.
Introduction -- The Psychology of Change -- The Modern Design Philosophy: Avoiding Change is Perilous -- Modern Design Philosophy: Organizational Considerations for Agile Systems Design -- A New Organization is needed: Beyond Integrated Product Teams -- Modern Design Methodologies: Information and Knowledge Management -- Agile, Robust Designs: Increasing Quality and Efficiency -- Conclusion: Modern Design Methodologies: Information and Knowledge Management.
Keywords: Engineering; Engineering design; Engineering; Engineering Design; Control; Innovation/Technology Management